Uji Perbandingan Aktivitas Antibakteri Ekstrak Daging Buah, Kulit Buah dan Daun Pala Hutan (Myristica Schifferi Warb) terhadap Escherichia Coli - Wiwi Rumaolat; Mohammad Dahlan Sely (Calory Journal Medical Laboratory Journal, 2024)
Nutmeg belongs to the Myristicaceae family which consists of 15 genera and 250 species. Nutmeg has several benefits for body health, namely, Improving brain health, Overcoming digestive problems, Maintaining oral health, Treating insomnia. Escherichia coli is a bacterial name taken from the name of the person who discovered it, Theodor Escherich. This study aims to determine the comparison of antibacterial activity of forest nutmeg pulp, peel and leaf extract (Myristica schifferi Warb) against Escherichia coli.: The research method used is the agar diffusion method. The results of the antibacterial activity test of the flesh and skin of forest nutmeg (Myristica schifferi Warb) against Escherichia coli bacteria with concentrations of 50%, 75% and 100% were declared sensitive to inhibit the growth of Escherichia coli bacteria. Meanwhile, the results of the forest nutmeg leaf test with a concentration of 50% were declared intermediate or medium category to inhibit the growth of Escherichia coli bacteria, for concentrations of 75% and 100% were declared sensitive to inhibit the growth of Escherichia coli bacteria.